한국식물병명목록 6.1판(2023 개정본) - 김선희(Seon-Hee Kim); 최재혁(Jaehyuk Choi); 최영준(Young-Joon Choi); 박병용(Byeong-Yong Park); 이수헌(Su-Heon Lee); 김경희(Gyoung Hee Kim); 공현기(Hyun Gi Kong); 김동근(Donggun Kim); 김순옥(Soonok Kim); 김영호(Youngho Kim); 백창기(Chang-Gi Back); 변희성(Hee-Seong Byun); et al. (Sigmulbyeong yeon'gu, 2023)
More than a year has passed after the 6th edition of 'List of Plant Diseases in Korea (LPDK)' was published in April 2022. The 6.1st edition (2023) of List of Plant Diseases in Korea was made by correcting errors found in the 6th edition of list and adding new diseases reported after the 6th edition. There were 397 corrections from the 6th edition, most of which were simple spelling errors or minor issues. However, 12 diseases were deleted due to duplication or unclear literature proof, and 2 diseases had their diseases' common names changed. We added 158 diseases that were reported before 2021 but not included in the 6th edition, or reported after the 6th edition. After all, 146 diseases were added to the 6,534 diseases in the 6th edition, resulting in a total of 6,680 diseases in the 6.1st edition. Thirty host taxa were also added, increasing the number from 1,390 in the 6th edition to 1,420 in the 6.1st edition. Pathogens were also added to 62 taxa, from 2,400 in the 6th edition, bringing the total to 2,462 taxa in the 6.1st edition. Ultimately, the 6.1st edition (2023) of 'The List of Plant Diseases in Korea' contains 6,680 diseases caused by pathogens of 2,462 taxa on 1,420 hosts. The 6.1st edition is not printed as a book, but is provided through the online 'List of Plant Diseases in Korea' (https://genebank. rda.go.kr/kplantdisease.do). 한국식물병명목록 6판이 2022년 4월에 발행된 이후에 1년이 경과하였다. 목록 6판에서 발견된 오류사항을 수정하고 6판 이후에 보고된 병을 추가하여 한국식물병명목록 6.1판(2023)을 작성하였다. 기존 6판의 수정사항은 397건으로 대부분은 단순 오탈자나 경미한 사항이었으나, 12개의 병은 중복이나 근거가 명확하지 않아 삭제하였고, 2개의 병은 병명을 바꾸었다. 2021년 이전에 보고되었으나 6판에 수록되지 않았거나, 6판 발행 이후에 보고된 158개의 병을 추가하였다. 결국 목록 6.1판에는 6판에 보고된 병 6,534개에 146개 병이 추가되어 총 6,680개의 병이 수록되었다. 기주 분류군도 30개가 더해져 목록 6판의 1,390개에서 6.1판에는 1,420개가 되었다. 병원체는 목록 6판의 2,400개에서 62개가 더해져 6.1판에는 2,462 분류군이 되었다. 결국 한국식물병명목록 6.1판(2023)은 1,420개의 기주에, 2,462 분류군의 병원체가 일으키는 6,680개의 병을 수록하고 있다. 목록 6.1판은 책으로 인쇄되지는 않고 온라인 한국식물병명목록(https://genebank.rda.go.kr/kplantdisease.do)을 통하여 제공되고 있다.